Bridging the Gap in Abstract Biology Concepts: A Needs Analysis for STEM-Integrated Argument-Driven Inquiry (ADI) Photosynthesis Learning - Fitriyani; Neni Hasnunidah; Kartini Herlina; Chansanah Diawati; Noor Fadiawati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze teachers' needs for the development of photosynthesis learning based on Argument-Driven Inquiry (ADI) integrated with the Science, Technology, Engineering, and Mathematics (STEM) approach as the basis for developing learning tools. The study was conducted at the needs analysis stage within the Design-Based Research (DBR) framework using a mixed methods approach with a sequential explanatory design. Quantitative data were obtained through a survey of 33 high school biology teachers in Lampung Province using a Guttman scale-based questionnaire, while qualitative data were obtained through in-depth interviews with three biology teachers. The results showed that 66.7% of teachers were not familiar with the ADI model and 54.5% had not implemented the STEM approach in learning. 90.9% of teachers had never used STEM-integrated ADI-based student worksheets, and 100% of teachers had never applied it to photosynthesis material. In addition, 75.7% of teachers had not measured critical thinking skills and 87.8% had not systematically measured collaboration skills. Interview results revealed that teachers still experience difficulties in understanding the implementation of ADI, integrating STEM in learning, developing appropriate learning tools, and facing obstacles such as the abstract nature of photosynthesis material, time constraints, and limited laboratory facilities. Based on these findings, it is recommended to develop a photosynthesis student worksheet based on STEM-integrated ADI equipped with critical thinking and collaboration assessment instruments to support more meaningful biology learning and oriented towards 21st-century skills.